A REVIEW ON MANUSCRIPTOLOGY – RETRIEVAL OF ANCIENT KNOWLEDGE (International Journal of Ayurveda and Pharma Research, 2019)
Manuscriptology/Palaeography/Codicology is the scientific and structural study of hand written document credited with fair antiquity. They are sources of cultural heritage and history. The treasure of wisdom has come down to people in the form of manuscripts. Written in different Indian languages they are spread all over the country in different institutions, libraries, monasteries and temples and in several private collections. Classification of manuscripts are based on the materials used for writing like palm leaf manuscript, paper manuscripts, birch bark manuscript, wood manuscript, Hansipatra manuscript, Talpatra manuscript etc and also the subject matter of the manuscripts like Vedas, Dharmasastra, Itihasa, Purana, Mahatmya, Darsana, Tantra, mantra, Ayurveda etc. Surveys for manuscripts in the past years identified many collections and newer collections must be identified and preserved. Conservation of manuscripts is carried out through 33 Manuscript Conservation Centres (MCCs), besides organizing preventive and curative conservation workshops at different locations of the country as per priorities. The National Database of Manuscripts, Kriti Sampada is available on the internet through the Mission's website. Manuscriptology is the process of conserving the future for the past. It keeps the pulse of the past. It preserves the literary, linguistic, artistic and cultural heritage. It is very essential to conserve the manuscripts. By conserving these manuscripts and using information contained in it will open a new horizon in fields of knowledge. So manuscript preservation and conservation is essential. Steps for these and types of manuscripts are detailed in this article.